2008
DOI: 10.1007/s11243-008-9174-8
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of the coupling reaction of aryl chlorides with bis(pinacolato)diboron by tricyclohexylphosphine-cyclopalladated ferrocenylimine complexes

Abstract: Tricyclohexylphosphine-cyclopalladated ferrocenylimine complexes were found to be very efficient catalysts for the one-pot borylation/Suzuki cross-coupling reactions of aryl chlorides with bis(pinacolato)diboron. Typically, using 0.5-1.0 mol% of catalyst in the presence of 3.0 equivalents of K 2 CO 3 as base in dioxane at 100°C provided the corresponding symmetrical biaryls in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In contrast to the well-established Miyaura borylation of aryl halides with diboronate esters as reagents (bis­(pinacolato)­diboron = B 2 pin 2 and others), the analogous direct introduction of Bdan boryl units from HBdan is much less explored . In fact, it was only recently that a chemoselective transfer of Bdan units from (pin)­B–B­(dan) to a series of aryl halides was reported .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the well-established Miyaura borylation of aryl halides with diboronate esters as reagents (bis­(pinacolato)­diboron = B 2 pin 2 and others), the analogous direct introduction of Bdan boryl units from HBdan is much less explored . In fact, it was only recently that a chemoselective transfer of Bdan units from (pin)­B–B­(dan) to a series of aryl halides was reported .…”
Section: Resultsmentioning
confidence: 99%
“…Additional palladacyclic catalyst precursors have been shown to be effective catalysts for the borylation of aryl halides and subsequent Suzuki–Miyaura reactions (Scheme ). Notably, two reports also demonstrated that aryl bromides can be generated and subsequently borylated in situ with N -bromosuccinimide as the brominating agent. , …”
Section: Boryl Substitutionsmentioning
confidence: 99%
“…Arylboronic acids and their esters are versatile and useful reagents in organic synthesis . Traditionally, arylboron compounds are prepared by transmetalation between arylmagnesium or aryllithium reagents and trialkylborates. ,, While the recently developed rhodium- and iridium-catalyzed direct borylation of arene C−H bonds represents a major breakthrough, the palladium-catalyzed cross-coupling of bis(pinacolato)diborane(4) (B 2 pin 2 ) (pin = pinacolato = OCMe 2 CMe 2 O) with aryl halides (eq ), reported by Miyaura et al in 1995, still represents one of the most important synthetic routes to arylboronates . The cost of B 2 pin 2 , however, led Masuda et al to develop an attractive, alternative palladium-catalyzed process using HBpin (eq 2).…”
Section: Introductionmentioning
confidence: 99%